Проблеми формування сприятливого інвестиційного клімату для інноваційного розвитку підприємств - Довбенко, В. І. (Видавництво Львівської політехніки, 2015)
Розглянуто проблеми формування сприятливих умов для нарощування інвестиційного потенціалу, орієнтованого на інноваційний розвиток підприємств. Розкрито роль інноваційної культури у формуванні сучасних кластерів, спроможних здійснювати перспективні НДДКР і забезпечувати успішну реалізацію інвестиційних проектів. Проаналізовано роль трансферу технологій і середовища сприйняття інновацій у формуванні належного інвестиційного клімату. Запропоновано заходи, що сприяють успішній комерціалізації результатів наукових розробок та їх просуванню на внутрішній та зовнішні ринки. The problems of formation the favourable conditions for increasing of investment potential, based on the innovative development of enterprises are considered. In the new conditions it is important reorient the thinking of management at finding new development opportunities. This requires special attention to innovation and involvement of all stakeholders in the process of forming values. The process of creating a commercially successful innovation involves new approaches to the management of the joint activity participants in the innovation process based on open access to information, effective knowledge sharing and joint formation of values that provides for the establishment of a new innovation culture. The complexity and high cost of large-scale R&D involves the active use of the results of other participants in the development of market innovation and thus setting up partnerships with them. Therefore, in the present conditions it is advisable to ensure the successful commercialization of scientific developments to use open innovation model, which involves establishing the climate of mutual understanding and trust of participants in the innovation process. The role of innovation culture consists in shaping of the modern clusters those are capable to perform advanced R&D and to ensure the successful implementation of investment projects. To enhance the cooperation between the parties in the process of commercialization the innovations appropriate to use the potential of clusters that allow forming a network of stable relations participants to establish effective technology transfer and provide a competitive advantage to innovative products. The role of technology transfer and environment for perception the innovation in shaping the investment climate is analyzed. The measures that contribute to successful commercialization of the results of scientific developments and their promotion to the domestic and foreign markets are proposed. Successful examples of collaboration between science, business, government and the crowd show a large number of scientific and technical associations and companies, including the Max Planck Society in Germany, General Electric in the United States and others are analyzed. Revealed, that an important task of the national economy is the creative solutions of problems intensify innovation activity based on the release of initiatives the scientists, researchers, business and society, eliminating of the barriers to the transfer of knowledge and technology to solving the specific problems of increase the efficiency of economic.
Problems of creating a favorable investment climate for innovative development of enterprises
Keywords: інноваційна культура; інвестиційний клімат; перспективні НДДКР та інвестиційні проекти; трансфер технологій; механізми підтримки інноваційного розвитку підприємств; innovative culture; investment climate; promising R&D and investment projects; technology transfer; mechanisms of support for the innovative development of enterprises